Themes in South-East Asian Newspaper Headlines on Rohingya Issue: Critical Discourse Analysis - Isti’anah, Arina (UIN Salatiga, 2019)
ABSTRACT Language is regarded as a tool to present the ideologies of its users, including how media portray particular issue in their headlines. Rohingya has gained much attention by media, including South-East Asian newspapers. The massive clearing done by Myanmar government triggers the attention of media. Headlines are regarded as the important element of news since their jobs are to attract the readers and frame the ideologies of the readers as well as the media themselves. This paper attempts at discussing how South-East Asian media present Rohingya in their headlines. Five newspapers were involved: The Jakarta Post from Indonesia, Malaysia Kini from Malaysia, Mmtimes from Myanmar, The Nation from Thailand, and Daily Star from Bangladesh, taken during 2017. The analysis was focused on the choice of Theme in the headlines as it is the departing message of the headlines. The approach conducted was Critical Discourse Analysis utilizing the textual function of language offered by Halliday. The analysis revealed that South-East Asian media had similarities and differences in portraying Rohingya issue. The similarities were seen from the reflected ideologies, responsibility and blame, and the types of employed Themes. The difference was found in the way each media portrayed the ideologies. However, all media agreed to show their responsibility to end and solve Rohingya crisis to achieve peace and harmony amongst South-East countries.Keywords: headlines, critical discourse analysis, Rohingya